THE EFFECT OF INTEGRATION BETWEEN SMART AUDIT AND GRACEFUL ACCOUNTING ON REDUCING THE COST OF PRODUCTS - Mohammed Frayyeh Hassan (American Journals, 2022)
This research aims to clarify the effect of integration between smart audit and graceful accounting to reduce the cost of products for industrial facilities and support their competitiveness. By defining the role of both smart auditing and the information resulting from it with the information resulting from graceful accounting and other information systems to provide a clear realistic view of the facility management about the costs of its products and the extent of its association with how its resources are consumed to support its competitiveness by controlling its products in a way that enhances improving its management.The researcher conducted a field study on a sample of Iraqi industrial establishments, using a survey form. Where the results of the field study indicated that achieving integration between smart audit and graceful accounting contributes to reducing the costs of products in industrial installations.
Keywords: smart audit, graceful accounting, reducing, cost, products.